2014
DOI: 10.5152/akd.2014.5115
|View full text |Cite
|
Sign up to set email alerts
|

How to estimate left ventricular hypertrophy in hypertensive patients

Abstract: Left ventricular hypertrophy (LVH) is a structural remodeling of the heart developing as a response to volume and/or pressure overload. Previous studies have shown that hypertension is not an independent factor in the development of LVH and occurrence does not depend on the length and severity of hypertension, but the role played by other comorbidities such as triglycerides, age, gender, genetics, insulin resistance, obesity, physical inactivity, increased salt intake and chronic stress. LVH develops through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 45 publications
0
13
0
8
Order By: Relevance
“…Echocardiographic diagnosis of LVH was made based on the left ventricular mass index (LVMI), which was calculated from measurements of interventricular septum thickness, posterior wall thickness of left ventricle, and end‐diastolic left ventricular diameter (Lovic et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Echocardiographic diagnosis of LVH was made based on the left ventricular mass index (LVMI), which was calculated from measurements of interventricular septum thickness, posterior wall thickness of left ventricle, and end‐diastolic left ventricular diameter (Lovic et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Left ventricular hypertrophy (LVH) is an important factor in the occurrence of cardiac remodeling and cardiovascular events [1]. Diabetes is a risk factor of LVH, which is independent of hypertension [2].…”
Section: Introductionmentioning
confidence: 99%
“…We found the incidence of coronary heart disease to be higher in the LVH(+) group, possibly because atherosclerosis patients are exposed to risk factors common to this condition and hypertensive LVH. Accumulating evidence has shown that LVH occurrence depends not only on hypertension duration and blood pressure levels, but also on other comorbidities, such as TG, age, gender, genetics, insulin resistance, obesity, physical inactivity, increased salt intake, and chronic stress, which play cooperative roles (Lovic et al, 2014). Besides these established risk factors, researchers have gradually begun to pay attention to the utility of certain inflammatory or oxidative mediators for early screening of populations at high risk of hypertension.…”
Section: Discussionmentioning
confidence: 99%